Costume design : the basics - Delligatti, T. M. (The basics, 2021)
"Costume Design: The Basics provides an overview of the fundamental principles of theatrical costume design, from pre-production through opening night. Beginning with a discussion of what is costume design, why do people wear clothes, and what is the role of the costume designer, this book makes accessible the art and practice of costume design. Peppered with interviews with working costume designers, it provides an understanding of what it means to be a costume designer and offers a strong foundation for additional study. Readers will learn: How to use clues from the script to decipher a character's wardrobe; Methods used to sketch ideas using traditional or digital media; How to discuss a concept with a team of directors, producers, and designers; Strategies to use when collaborating with a professional costume shop; How to maintain a healthy work/life balance; Courses of action when working under a limited money and labor budget. Costume Design: The Basics is an ideal starting point for aspiring designers looking for ways to achieve the best costumes on stage and realize their vision into a visual story told through clothing"--